Effect of Combined Extrusion and Rolling Parameters on Mechanical and Corrosion Properties of New High Strength Al-Mg Alloy - Kweon-Hoon Choi; Bong-Hwan Kim; Da-Bin Lee; Seung-Yoon Yang; Nam-Seok Kim; Seong-Ho Ha; Young-Ok Yoon; Hyun-Kyu Lim; Shae-Kwang Kim (Metals, 2021)
High strength Al-Mg alloy is an attractive material that has the characteristic of increasing both strength and elongation by adding more solute Mg. However, there is a limitation in the oxidation issue during the casting process when it contains high amounts of solute Mg. New Al-Mg alloy was developed using Mg+Al2Ca master alloy by making a stable CaO/MgO mixed layer that no significant oxidation occurred. Here, the intergranular corrosion (IGC), electrochemical, and mechanical properties of new Al-Mg alloys fabricated through a combined process of extrusion and cold rolling were studied after the specimens went through artificial aging heat treatment at 200 °C. The results show that the grain size and the volume fraction of anodic β-precipitation (Mg2Al3) forming on the grain boundary influence the intergranular corrosion results. Corrosion potential and current density were achieved by potentiodynamic polarization electrochemical test. The results show that corrosion potential remains irrespective of the manufacturing process, while current density increases with artificial aging treatment. Both hardness and tensile mechanical properties decrease on cold rolled specimens after the heat treatment, while increase in extrusion and annealed specimens.